Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/0471142727.mb1630s108
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Cell‐Free Protein Synthesis: Historic Landmarks, Commercial Systems, and Expanding Applications

Abstract: During early days of molecular biology, cell-free protein synthesis played an essential role in deciphering the genetic code and contributed to our understanding of translation of protein from messenger RNA. Owning to several decades of major and incremental improvements, modern cell-free systems have achieved higher protein synthesis yields at lower production costs. Commercial cell-free systems are now available from a variety of material sources, ranging from “traditional” E. coli, rabbit reticulocyte lysat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 121 publications
1
45
0
1
Order By: Relevance
“…The first reported in vitro artificial incorporation of carboxy radio-labeled amino acids into proteins from rat liver cells extracts took place in 1948, 145 and more generally, since the early 1950s, 146 it has been shown that disrupted cells from both eukaryotes 147 or prokaryotes 148,149 are still capable of synthesizing proteins. Based on these observations, "cell-free translation" systems have been developed and used to obtain minute amounts of labeled proteins for identification or characterization in the laboratory setting.…”
Section: Cell-free Translation: a Dizzying Scaling-upmentioning
confidence: 99%
See 1 more Smart Citation
“…The first reported in vitro artificial incorporation of carboxy radio-labeled amino acids into proteins from rat liver cells extracts took place in 1948, 145 and more generally, since the early 1950s, 146 it has been shown that disrupted cells from both eukaryotes 147 or prokaryotes 148,149 are still capable of synthesizing proteins. Based on these observations, "cell-free translation" systems have been developed and used to obtain minute amounts of labeled proteins for identification or characterization in the laboratory setting.…”
Section: Cell-free Translation: a Dizzying Scaling-upmentioning
confidence: 99%
“…In general, these systems are derived from cells engaged in a high rate of protein synthesis, and commercially available systems exist for various applications including ribosome display and unnatural amino acid incorporation. 146 The development of cell-free systems depends upon both qualitative and quantitative considerations. Qualitative control may be achieved through use of insect cells, 153,154 or HeLa cells, 155 to overcome improper protein folding or glycosylation.…”
Section: Cell-free Translation: a Dizzying Scaling-upmentioning
confidence: 99%
“…Typical cell‐free expression systems include rabbit reticulocyte, wheat embryo, and Escherichia coli cell extract enriched with energy constituents and free amino acids (Wiegand, Lee, Ostrov, & Church, 2019). For instance, a bacterial cell‐based CFPS system embodies the bacteria lysate, DNA, and energy modules (creatine phosphate, glucose‐6‐phosphate, phosphoenolpyruvate, glucose) all of which could be optimized to obtain higher efficacy (Chong, 2014). Therefore, such supple system with its efficiency being eminently dependent on active cytoplasmic extracts could be applied as a striking tool for protein production in an uncomplicated batch‐format reaction in vitro (Caschera, 2017).…”
Section: Cfps: From Test Tube Reactions To Cell‐free Expression In MImentioning
confidence: 99%
“…Sophisticated protocols of bacterial cell-free protein synthesis system have been established as coupled transcription-translation systems with exogenous DNA (7,8). Due to advanced developments, such as a continuous-flow system that provides reaction solutions with essential substrates and energy sources (9) and the PURE (protein synthesis using recombinant elements) system that is reconstituted by purified ribosomes and well-known translation-related factors (10,11), the cellular machinery of protein synthesis can now be prepared and reconstituted from various organisms in the laboratory or obtained from commercial suppliers (3,12).…”
mentioning
confidence: 99%